A preliminary examination of the validity and reliability of a new brief rating scale for symptom domains of psychosis: Brief Evaluation of Psychosis Symptom Domains (BE-PSD). (September 2016) - Takeuchi, Hiroyoshi; Fervaha, Gagan; Lee, Jimmy; Agid, Ofer; Remington, Gary
Abstract: Background: Brief assessments have the potential to be widely adopted as outcome measures in research but also routine clinical practice. Existing brief rating scales that assess symptoms of schizophrenia or psychosis have a number of limitations including inability to capture five symptom domains of psychosis and a lack of clearly defined operational anchor points for scoring. Methods: We developed a new brief rating scale for five symptom domains of psychosis with clearly defined operational anchor points – the Brief Evaluation of Psychosis Symptom Domains (BE-PSD). To examine the psychometric properties of the BE-PSD, fifty patients with schizophrenia or schizoaffective disorder were included in this preliminary cross-sectional study. To test the convergent and discriminant validity of the BE-PSD, correlational analyses were employed using the consensus Positive and Negative Syndrome Scale (PANSS) five-factor model. To examine the inter-rater reliability of the BE-PSD, single measures intraclass correlation coefficients (ICCs) were calculated for 11 patients. Results: The BE-PSD domain scores demonstrated high convergent validity with the corresponding PANSS factor score ( r s  = 0.81–0.93) as well as good discriminant validity, as evidenced by lower correlations with the other PANSS factors ( r s  = 0.23–0.62). The BE-PSD also demonstrated excellent inter-rater reliability for each of the domain scores and the total scores (ICC(2, 1) = 0.79–0.96). Conclusions: The present preliminary study found the BE-PSD measure to be valid and reliable; however, further studies are needed to establish the psychometric properties of the BE-PSD because of the limitations such as the small sample size and lacking data on test-retest reliability or sensitivity to change.